DIGITAL FOLKTALES AND CULTURALLY RESPONSIVE TEACHING (CRT): A LITERATURE REVIEW ON ENHANCING YOUNG LEARNERS ENGLISH THROUGH LOCAL NARRATIVES AND TECHNOLOGIES - Husin; Amelia (Vol. 3 No. 1 (2025): Proceeding of International Conference on Cultures & Languages 2025)
This paper presents a literature review examining recent scholarly works on the integration of local folktales into English language instruction for young learners, framed within the principles of Culturally Responsive Teaching (CRT) and supported by digital storytelling technologies. The purpose of this review is to synthesize theories, frameworks, and empirical findings from credible and up-to-date journals, with the aim of identifying key insights relevant to the subtheme Innovation in Language Education in the Digital Era. The reviewed literature covers three main areas: (1) the pedagogical value of folktales in fostering linguistic competence and cultural identity, (2) the effectiveness of digital storytelling tools such as animated videos, interactive e-books, and audio platforms in supporting young learners’ language skills, and (3) the role of CRT in creating inclusive and culturally meaningful learning environments. Through comparative analysis of multiple studies, the paper highlights common themes, emerging trends, and research gaps. The conclusion offers synthesized implications for curriculum design, teacher professional development, and the implementation of low-cost digital storytelling practices in bilingual primary education. This review aims to provide a theoretically grounded and evidence-based perspective for educators and policymakers seeking to integrate cultural heritage and digital innovation into English language teaching for young learners.